Impact of the app-based and nurse-led supportive care program AKO@dom on dose intensity of oral-targeted therapies in patients with metastatic renal cell cancer: a multicentric observational retrospective study - Gaillard, Victor; Lhuillier, Albane; Bigot, Cécile; Pierard, Laure; Trensz, Philippe; Burgy, Mickael; Schuster, Caroline; Malouf, Gabriel; Fritsch, Aurélie; Lang, Hervé; Tricard, Thibault; Borchiellini, Delphine; et al. (Supportive care in cancer, 2022)
Background Tyrosine kinase inhibitors (TKIs) remain a cornerstone of metastatic kidney cancer (mRCC). Adverse events (AEs) may lead to dose downregulation, and optimal management of AEs is needed to maintain an efficient dose intensity (DI). The aim of our study was to evaluate the impact of an app-based and nurse-led supportive-care program on DI in mRCC patients. Method This multicenter ( n = 3), retrospective study evaluated all consecutive mRCC patients who participated in the AKO@dom program, which consisted of an app-based and nurse-led weekly patient evaluation at home during the first 3 months of TKI intake. Treatment patterns and modifications were described, and the mean DI (mDI) was calculated at the end of AKO@dom. Results Eighty-nine patients were included: 12 had sunitinib, 18 pazopanib, 12 axitinib, and 47 cabozantinib. Median age was 69 years (60–76). TKIs were mainly initiated at standard doses except for cabozantinib (53% started at 40 mg/day); 71% had prior systemic treatment. Nine patients discontinued permanent treatment during the program. Thirty-two patients required ≥ 1 dose interruption, and 29% experienced ≥ 1 grade 3 AE of any type. The mDI (in mg/day) at 3 months was 34.4 ± 17.7 for sunitinib, 672.8 ± 144 for pazopanib, 8.6 ± 2.6 for axitinib, and 40 (36–48) for cabozantinib. Fifty-five patients [68.75% (95% CI: 57–78%)] had a mDI ≥ than reported in the literature. Overall survival at 12 months was 64.2% (CI 95%: 55–75%). Conclusion The AKO@dom program allowed 68.75% of patients to maintain a high dose intensity after 3 months of TKI treatment. The impact on survival outcomes needs to be evaluated in randomized clinical trials.